Influence of Arduino on the Development of Advanced Microcontrollers Courses (2017)
This paper describes the development of courses in the field of digital design that use Arduino boards as their main platforms. Arduino offers an intuitive development environment and multiple hardware and software resources that allow rapid development of microcontroller-based projects. However, due to the vast amount of information available, students were losing the capability to design their own prototypes. We propose a methodology that introduces the study of microcontrollers using Arduino to develop different types of projects and proceeds to study the system architecture to gain control on the device. This methodology has been used in an undergraduate course in microcontrollers and a graduate course in advanced techniques in digital design. The students of the microcontrollers course showed improved design skills and motivation compared to the students from previous versions of the course. With respect to the advanced techniques in digital design course, the students were able to take advantage of Arduino platform to gain a deep understanding of hardware/software co-design of embedded systems. © 2013 IEEE.